Collaboration in government : forms and practices - McNabb, David E.; Swenson, Carl R. (New York, NY : Routledge, 2021)
"This book comprehensively explore the many different forms of collaboration in government, both formal and informal, including strategic alliances, intergovernmental networks, and public-private partnerships. Contemporary US governmental and public organizations are changing to better cope after several decades of pressures to downsize, as well as to deliver new services with declining resources and, in many cases, decaying infrastructure. To meet these challenges, public managers are developing new networks, partnerships, collaborations, alliances and coalitions to deliver government services. Collaboration in Government is designed to help public organizations parse the new and emerging forms of public partnerships and to develop the skills needed to manage them. Each chapter offers examples of how each type has been used in real public organizations, providing the reader with an understanding of how these partnerships may be applied in a variety of contexts, as well as lessons that may be gleaned from the successes (and failures) of these collaborative models"--
Introduction to collaborative governance -- Government partnerships -- Partners with the public -- Public sector collaborations -- Co-management and adaptive co-management -- General agreements and coalitions -- Grants and cooperative agreements -- Strategic alliances -- Intergovernment networks -- Managing networks -- Public/private partnerships -- Government outsourcing and co-sourcing.
OCLC-licensed vendor bibliographic record.
Keywords: Interagency coordination -- United States; Intergovernmental cooperation -- United States; Public-private sector cooperation -- United States; Interorganizational relations -- United States; Contracting out -- United States; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General